Affected Microcirculation and Vascular Hemodynamics in Takayasu Arteritis - Svensson, Christina; Bjarnegård, Niclas; Eriksson, Per; Jonasson, Hanna; Strömberg, Tomas; Sjöwall, Christopher; Zachrisson, Helene (Frontiers in Physiology, 2022)
Abstract Introduction: Takayasu arteritis (TAK) is a rare inflammatory disease affecting aorta and its major branches. Ultrasound (US) can detect inflammatory features in the arterial wall, but less is known regarding skin microcirculation and vascular hemodynamics. The aim was to study if assessment of these variables could add valuable information regarding vascular affection in TAK. Methods: 17 patients diagnosed with TAK and 17 age- and sex- matched healthy controls were included. Microcirculatory peak oxygen saturation (OxyP) in the skin after induced ischemia was evaluated with laser Doppler flowmetry/diffuse reflectance spectroscopy. Cerebrovascular reserve capacity (CVR) in the brain was assessed with transcranial Doppler (TCD). Pulse waves were recorded in the radial artery by the aid of applanation tonometry, for calculation of central augmentation index (AIx75). Intima media thickness (IMT) and stenosis/occlusions were evaluated using US in carotid and central arteries. Results: Reduced OxyP (79±8 % vs. 87±4 %, p<0.001) was seen in patients with TAK regardless of significant arterial stenosis/occlusion or not. Increased AIx75 (22.3±13.6 vs. 9.2±16.3, p=0.01) was seen in TAK patients without significant stenosis/occlusions. No differences were found in CVR, regardless of proximal stenosis. However, signs of a more high-resistance flow profile were seen in arteria cerebri media. Conclusion: Regardless of arterial stenosis or not, impaired microcirculation of the skin and preserved CVR in the brain were found in subjects with TAK. Signs of increased arterial stiffness in the brain and central arteries were observed. The value of these findings for prediction of future cardiovascular events needs to be clarified in further studies.